Family Resilience in the Family of a Terrorist - Akbar, Zarina; Fujiati, Indah (Jurnal Psikologi, 2021)
Acts of terrorism carried out by terrorists have an impact on the families of the terrorists, especially if their familiesremain stay in their environment. The families of the terrorists experience many changes following the terrorismcommitted by their family member(s) and even putting the families in a crisis. This research aims to obtain adescription of family resilience in the families of terrorists following a terrorism. This research uses a qualitativeapproach with a case study method. The data collection techniques used were direct observation and interviewwith the family (both parents of the terrorist/perpetrators). Data triangulation was done with the significant others(cousins of the terrorist/perpetrator and local public figures). The research subjects were a particular familyconsisting of a father, a mother, and a child (the child was the perpetrator of a terrorism). The results showed thatthe resilience aspects of the belief system in the family of the terrorist can interpret all events well, organizationalpatterns that can adapt to situations but with a less open communication to one another. The family of the terroristhave gone through the process of becoming resilient and have used the strength and resources available to thefamily to increase resilience in the family, especially with respect to the social stigma of society given to thefamily following the terrorism.